Visual Narrative Techniques In Delivering Visual Experience: A Case Study Of Jimmy Liao's Picturebook - Loo, Yih Charn (2017)
Visual narrative is the subgenre of visual studies and visual narratives have long existed as a form of entertainment. They are usually referred in more specific terms such as animation, films, comics and picturebooks. In the heat of Malaysia’s government effort in investing in the creative content industry, the effort to raise the standards of the creative industry should be supported by research in visual narratives. In order to further understand the working of visual narratives, this research seeks to address the lack of documentation of techniques in static visual narratives.